Democracy and its discontents in post-wall Germany - Hofferbert, Richard I.; Klingemann, Hans-Dieter (2000)
Abstract: "This paper traces the political behavior intentions of 'satisfied democrats', 'dissatisfied democrats', and 'non-democrats' in western and eastern Germany. Dissatisfaction is most commonly expressed in support for the loyal opposition, with some minor tilt toward parties of the ends of the spectrum. Non-democrats, a very small percentage of the populace, more commonly express their disapproval through withdrawal rather than through active extremism. Based on a 1997 general population survey, the analysis reveals some differences in the magnitude of western versus eastern conceptions of the elements that make up 'democracy'. But most of those differences get channeled into seemingly benign forms of political participation. The core of the findings is that dissatisfaction with democracy may well be a healthy stimulant rather than a threat to the vitality of either established or emerging democracies." (author's abstract)